If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(n/3)+(3/4)=(5/6)n-1
We move all terms to the left:
(n/3)+(3/4)-((5/6)n-1)=0
Domain of the equation: 6)n-1)!=0We add all the numbers together, and all the variables
n!=0/1
n!=0
n∈R
(+n/3)-((+5/6)n-1)+(+3/4)=0
We get rid of parentheses
n/3-((+5/6)n-1)+3/4=0
We calculate fractions
24n^2/72n+()/72n+324n/72n=0
We multiply all the terms by the denominator
24n^2+324n+()=0
We add all the numbers together, and all the variables
24n^2+324n=0
a = 24; b = 324; c = 0;
Δ = b2-4ac
Δ = 3242-4·24·0
Δ = 104976
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{104976}=324$$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(324)-324}{2*24}=\frac{-648}{48} =-13+1/2 $$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(324)+324}{2*24}=\frac{0}{48} =0 $
| 5x+(1.04-5x)=1.04 | | -2(5t-2)+8t=5t-2 | | -v+29=174 | | 12+(t-5)=0 | | 115/30=x/6 | | 50-y=269 | | -x/5-46=-39 | | -5(y+3)+3(3y-7)=3(y-4)+10 | | x^2/3-4=5 | | -4w+5=w+2-6w-4w+5=w+2-6w | | 15-(6-7r)=2+6r | | X+0.09x=140 | | 8/11n=564/11 | | 8y+7=3y-4 | | 4x+3(2x-5=45 | | -2.4y+5=29 | | 2/3-(n*5/8)=7/12 | | 2t+5=35 | | 7x+149=180 | | 9x+4x=63 | | 9g+11=-13 | | 12p-8=6p+5 | | 1/3(y-3)=1/4(y+4) | | 11x=100*12 | | 0.02(y-4)+0.12y=0.04y-0.01(20) | | -62+62=-23p-15p | | 2n=242/5 | | x+24=36;x | | .72727(n-10)=64 | | 3x+4=(3x+2) | | r^2-5r+6=5 | | 3(b+4+8=-3 |